Regulation of the fetal hemoglobin silencing factor BCL11A - Basak, Anindita (Ann N Y Acad Sci, 2016)
The clinical severity of sickle cell disease and β-thalassemia, the major disorders of β-globin, can be ameliorated by increased production of fetal hemoglobin (HbF). Here, we provide a brief overview of the fetal-to-adult hemoglobin switch that occurs in humans shortly after birth and review our current understanding of one of the most potent known regulators of this switching process, the multiple zinc finger–containing transcription factor BCL11A. Originally identified in genome-wide association studies, multiple orthogonal lines of evidence have validated BCL11A as a key regulator of hemoglobin switching and as a promising therapeutic target for HbF induction. We discuss recent studies that have highlighted its importance in silencing the HbF-encoding genes and discuss opportunities that exist to further understand the regulation of BCL11A and its mechanism of action, which could provide new insight into opportunities to induce HbF for therapeutic purposes.